2017
DOI: 10.1111/crj.12675
|View full text |Cite
|
Sign up to set email alerts
|

Can ADMA play a role in determining pulmonary hypertension related to chronic obstructive pulmonary disease?

Abstract: The mean age of patients was 69.21 ± 10.62, and 15 of these patients were females. There was no significant difference between the two COPD groups in terms of age and sex (P > .05). There was no difference in PaO , SaO , FEV and FEV /FVC values between the two COPD groups (P > .05). Serum ADMA levels were similar in the control and the COPD group (0.42 ± 0.13 vs 0.43 ± 0.15), but it was significantly higher in the COPD-PH group compared to the control and the COPD group (0.49 ± 0.14). A negative correlation wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 29 publications
0
18
0
Order By: Relevance
“…65 In patients with chronic obstructive pulmonary disease, ADMA may help in the determination of the presence of PH. 63 In patients with CTEPH, elevated ADMA levels were associated with mean right atrial pressure, cardiac index, and mixed venous oxygen saturation. 62 Zhang et al observed similar tendency in their study, wherein patients with both CTEPH and PAH had significantly higher ADMA levels than the control group.…”
Section: Asymmetric Dimethylargininementioning
confidence: 94%
“…65 In patients with chronic obstructive pulmonary disease, ADMA may help in the determination of the presence of PH. 63 In patients with CTEPH, elevated ADMA levels were associated with mean right atrial pressure, cardiac index, and mixed venous oxygen saturation. 62 Zhang et al observed similar tendency in their study, wherein patients with both CTEPH and PAH had significantly higher ADMA levels than the control group.…”
Section: Asymmetric Dimethylargininementioning
confidence: 94%
“…In another study, Telo et al. 20 compared patients with chronic-obstructive lung disease (COPD) who had developed PAH (defined as systolic PAP (sPAP) > 35mm Hg) to COPD patients without elevated sPAP and to healthy controls. They found a significantly elevated mean ADMA concentration in COPD patients with PAH as compared to both other groups.…”
Section: Adma Is Increased In Hypoxia and In Pah: Observational Humanmentioning
confidence: 99%
“…The scenario is further acerbated by the significantly reduced plasma arginine concentrations in patients with renal failure in comparison to healthy patients [95]. Of pathophysiological significance, elevated circulating plasma concentrations of ADMA provide a marker of risk for a wide range of endothelial dysfunction and renal and cardiovascular disorders, such as renal failure, chronic obstructive pulmonary disease (COPD) such as pulmonary arterial hypertension [97], pulmonary fibrosis, rheumatoid arthritis (RA) [98], increased cardiovascular morbidity and mortality, diabetes, heart failure, and elevated systemic blood pressure [54,99,100]. High plasma ADMA was correlated with high all-cause mortality and late mortality in renal transplant recipients.…”
Section: Adma—the Small Molecule Metabolite Product Of Arginine Mementioning
confidence: 99%